PHD Finger Protein 19 Enhances the Resistance of Ovarian Cancer Cells to Compound Fuling Granule by Protecting Cell Growth, Invasion, Migration, and Stemness - Ruan, Shanming; Zhang, Haizhong; Tian, Xinxin; Zhang, Zhiqian; Huang, Hong; Shi, Chao; Liu, Wenhong; Jiang, Xiawei; Huang, Dawei; Tao, Fangfang (Frontiers in Pharmacology, 2020)
Ovarian cancer is one of the most common gynecological malignancies in women worldwide with a poor survival rate. We have previously reported that compound fuling granule (CFG), a traditional Chinese medicinal preparation used to treat ovarian cancer in China for over twenty years, significantly promotes cell cycle arrest, apoptosis, senescence, TGFβ-induced invasion and migration, tumor growth and distant metastasis in ovarian cancer cells. However, the underlying mechanisms are not clear. In the present study, we found that PHF19 expression in ovarian cancer cells positively correlated with their resistance ability to CFG. In addition, PHF19 overexpression increased the resistance of HEY-T30 and SKOV3 cells to CFG, while knockdown of PHF19 enhanced their sensitivity to CFG. Moreover, CFG significantly inhibited the expression of PHF19 both in mRNA and protein levels in these cells. Gain of function and loss of function experiments further proved that PHF19 is a crucial mediator involved in the ovarian cancer progression, including cell proliferation, invasion, migration and stemness. Importantly, rescue the expression of PHF19 reverted CFG-induced suppression in ovarian cancer cell growth, EMT and stemness, while PHF19 knockdown accelerated CFG’s anti-tumor effect. Overall, our results provide a series of evidence to reveal that PHF19 is critical suppressor for CFG's anti-tumor effect in ovarian cancer.